Global Eclectic Treatment of Covid-19: Global, Regional, and National Perspectives on Common Enemy - Anadza, Hirshi; Pasopati, Rommel Utungga; Syarifuddin, Syarifuddin (Nation State: Journal of International Studies, 2021)
After being called the UN's, COVID-19 has become a global common enemy today. The escalation of the pandemic has been responded to nationally, regionally, as well as globally. However, the efforts of the United Nations as the most significant international organization are interpreted differently at the regional and national levels. That way, there will be a gap in understanding between the handling of COVID-19 at the global, regional, and national levels. Therefore, this paper discusses further how the COVID-19 as a common global enemy is reflected in regional and national actions against this pandemic? The global eclectic theory is explored to explain how global concepts relate to more specific concepts. Comparing the COVID-19 handling policies in ASEAN, SAARC, and the EU is needed to deeply explain the differences in handling the outbreak in each region. The result shows that common enemies do not automatically reflect joint regional action. National interest is still challenging to consolidate at the regional, furthermore global level. Moreover, cultural differences between countries cannot be reduced quickly in global matters.